2014
DOI: 10.5539/ijms.v6n4p10
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Service Quality and Customer Satisfaction in Hypermarkets of Saudi Arabia

Abstract: The objective of this study is to determine the perception of retail service quality and its relationship with satisfaction for customers of hypermarkets in the Kingdom of Saudi Arabia (KSA). Data was collected through self-administered questionnaires using convenience sampling technique. Out of 220 responses, 185 were finally chosen and analyzed for descriptive statistics as well as significant relationship between hypermarket service quality and customer satisfaction. The respondents reported high levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 77 publications
5
17
0
1
Order By: Relevance
“…Bazaar. The findings are consistent with studies [3,5] which found the significance of better service quality to increase customer satisfaction. As the college students are not an earning member of the family and still depend on their parents for shopping, the purchase trends among them may vary and also may be affected by the labeled prices.…”
Section: Resultssupporting
confidence: 82%
“…Bazaar. The findings are consistent with studies [3,5] which found the significance of better service quality to increase customer satisfaction. As the college students are not an earning member of the family and still depend on their parents for shopping, the purchase trends among them may vary and also may be affected by the labeled prices.…”
Section: Resultssupporting
confidence: 82%
“…SERVQUAL scale has been widely and constructively deployed in various and many private research studies (Parasuraman et al, 1991(Parasuraman et al, , 2002. According to Muhammad et al (2011), Vanniarajan and Gurunathan (2009), Khan and Fasih (2014) and Mahfooz (2014) the scale is widely and positively discussed in various prominent published research studies and Ashdaq et al (2015); Jain and Gupta (2004); Omar et al, (2015); Thongthip and Polyorat (2015) insure its reliability and validity. On the basis of criticism made on SERVQUAL scale, proper and well defined refinements were made (Parasuraman et al, 1991).…”
Section: Service Qualitymentioning
confidence: 99%
“…Other studies proved that service quality has a positive impact to customer satisfaction ( [6]; [9]; [1]; [2]). Therefore, we propose the following hypothesis:…”
Section: Service Qualitymentioning
confidence: 99%